The Implication of Merdeka Belajar on the Evaluation of Islamic Religious Education Learning - Andy Riski Pratama; Aprison, Wedra; Irsyad, Wilda; Hidayat Hasan, Rahmat (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2024)
This article is prepared to examine the form of the policy of the Minister of Education and Culture of the Republic of Indonesia and its implications for the development of Islamic religious education (PAI) evaluation. The research method used in writing this article is a qualitative method with a literature study approach. In the literature study, data are collected through a process of review, analysis, and presentation of results. Based on the literature review, the Ministry of Education and Culture's policy is known as Merdeka Belajar policy. This policy includes 4 things: a national standardised school exam (USBN) developed by each school; the national exam (UN) is changed to a minimum competency assessment and character survey; freedom for educators to design lesson plans (RPP); and flexibility in new student admission regulations (PPDB). Merdeka Belajar policy has characteristics that emphasise creativity, learning orientation towards problem solving, learning based on the demands of society and the world of work, and a comprehensive assessment system. This has an impact on the need to develop PAI learning evaluation. The conclusions of this article are: Evaluation development is based on the purpose of human creation as 'abdun and khalīfah; PAI learning evaluation includes aspects of 'aqliya, batinya, and amaliya. The evaluation of PAI learning is carried out to balance the power of thinking, dhikr, and charity.